بتعـلّم مـــهاراتها في تعليـم اللغــة العـربية - Suharmon Suharmon (Universitas Islam Negeri Mahmud Yunus Batusangkar, 2010)
Evaluation is aimed at figuring out whether predetermined purposes have been successfully met and to decide what instructional materials and competency should be achieved by the students. In the context of Arabic learning, such instructional materials and competency should be relevant to the evaluation. Consequently, evaluating speaking skill by means of reading test will never take place. In this context, language learners should understand the interrelationship between language testing (evaluation) and language skill mastery, especially in Arabic learning evaluation. Kata kunci: اختبارات اللغة, مهارات اللغة, تعليم اللغة, تعلم مهارات اللغة,عملية الاختبارات